Establishment and identification of an animal model of long-term exercise-induced fatigue - Yan, Kai; Gao, Haoyang; Liu, Xiaohua; Zhao, Zhonghan; Gao, Bo; Zhang, Lingli (Frontiers in Endocrinology, 2022)
In competitive sports, the training load is close to the human physiological limit, which will inevitably lead to sports fatigue. If fatigue can not be recovered in time, it will even lead to excessive training and affect the improvement of sports ability. Therefore, fatigue has become an important part of physical function assessment of athletes. As a research hot spot in the field of international sports, sports fatigue still lacks a clear definition and classification. This paper puts forward that exercise-induced fatigue is divided into temporary and long-term, summarizes the preparation of animal models of exercise-induced fatigue, and summarizes and compares the modeling schemes of mice under treadmill and swimming. Summarizes the phenotype of multiple organs after long-term exercise fatigue, such as myocardial cell damage, bone mineral density changes, skeletal muscle damage, demonstrates the adverse effects of long-term exercise fatigue; finally, the indicators of fatigue are analyzed, which are mainly divided into exhaustion time, organ index and biochemical indicators. The relationship between these physiological and biochemical indicators and exercise fatigue is summarized and analyzed to promote the monitoring of exercise fatigue. It attempts to provide a reference for the establishment of animal models of sports fatigue, and provide a new theoretical basis for medical supervision and recovery of sports fatigue in the future, in order to improve the performance of athletes.